Hidden Hout Bay mainstream, myths and margins - Luckett, Sidney (Centre for Film and Media Studies, 2019)
This essay, which accompanies a photo-book, constructs a different picture which I have made of Hout Bay; a picture that lies behind the glossy postcard and calendar photographs of this global tourist attraction; one that lies hidden from foreign tourists as well as from local visitors to the harbour, who are attracted by sunset trips into the bay and ‘locally harvested’ sea-food ‘fresh from the sea’ eateries. Using a photographic metaphor this picture is an overlay of three ‘negatives’ and like the negatives used in film photography, they need to be ‘developed’ before they can be seen by the eye of a casual passer-by who might gaze upon them in an exhibition. However a photographer knows that (the process of) developing a negative can be halted at any point that she chooses and what is revealed is what she already had in her minds-eye as the significant idea that she wants to communicate (which may or may not be what the passer-by sees). This is an apt metaphor for the three sections of this essay– each of the three central sections are in the process of being developed and what is read now is nothing more than a moment in their development. Like any overlay they need to be seen in combination to make the sense that the photographer (myself) wishes to communicate. But unlike most overlays, this overlay is comprised of three ‘negatives’ that in each case have been halted the process of their development. These three transparencies are: Firstly of my adventure in a political praxis that has traversed social activism, academia as a rural/environmental economist and currently involves photographically documenting the lives of the people of Hangberg (Hout Bay), squeezed between the iconic Sentinel peak and Mariners Wharf (an important tourist attraction) on the Hout Bay harbour. The second transparency is an account of the development of documentary photography, a much contested enterprise (Rosenblum 1997, Marien 2002, Golden 2005, Abbott 2010), using Habermas’ three knowledge constitutive interests (Habermas 1981, Habermas 1985) as an indicative framework. The third is an analysis of the socio-political context of Hangberg that draws together political theories that have their roots in Antonio Gramsci’s (Gramsci 1971, Simon 1991) notion of the subaltern, most notably the Subaltern Studies Group in Calcutta formed by Gayatri Spivak and exemplified in Partha Chattterjee’s (Chatterjee 2000, Chatterjee 2004, Chatterjee 2011) distinction between political and civil societies, Asef Bayat’s (Bayat 2013, Bayat 2013) quiet encroachment of the ordinary, Hardt and Negri,’s (Hardt 2009, Hardt 2017) perspective on the commons, as well as Murray Li’s (Li 2007, Li 2014), Shiva’s (Shiva 1988) and Scott’s (Scott 1998, Scott 2009) (re)thinking about capitalist modernity.